SPECIAL PERIODS OF ANTHROPONYMS FORMATION IN ENGLISH AND UZBEK LANGUAGES (Journal of Universal Science Research, 2025)
This work highlights the different periods inherent in the formation of names that exist in English and Uzbek languages. The role of anthroponyms in the field of onomastics is mentioned.